The Impact of Financing Restructuring Policy on Financial Performance and Islamic MSME Financing during Covid-19: A Study of Indonesian Islamic Commercial Banks - Safira , Zahra; Badina, Tenny; Pardiansyah, Elif (Universitas Al-Qolam Malang, 2024)
The purpose of this study was to determine the differences in Return on Assets (ROA), Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO), as well as Islamic MSME Financing at Islamic commercial banks in Indonesia before and after the implementation of the financing restructuring policy during the Covid-19 period. The research method used to analyze is a comparative method with a quantitative approach calculated using the Paired sample t-test if the data is normally distributed and the Wilcoxon signed rank test if the data is not normally distributed which is carried out using IBM SPSS 25 software. The results showed that there were significant differences in financial performance as seen in the ratios of ROA, NPF, CAR, FDR, and BOPO before and after the implementation of the financing restructuring policy during the Covid-19 period. Meanwhile, Islamic MSME financing has no difference before and after the implementation of the financing restructuring policy during the Covid-19 period. Overall, the restructuring policy has a positive impact on the financial health of Islamic Commercial Banks, while maintaining stable support for Islamic MSME financing in Indonesia.